Clinical and cost effectiveness of a multi‐professional medication reviews in care homes (CAREMED). (14th July 2020) - Desborough, James A.; Clark, Allan; Houghton, Julie; Sach, Tracey; Shaw, Val; Kirthisingha, Viveca; Holland, Richard C.; Wright, David J.
Abstract: Objectives: With 70% of care home residents experiencing a medication error every day in the UK, better multi‐professional working between medical practitioners, pharmacists and care homes was recommended. The aim of this study was to determine the effectiveness (falls reduction) and cost‐effectiveness, of a multi‐professional medication review (MPMR) service in care homes for older people. Method: A total of care homes in the East of England were cluster randomised to 'usual care' or two multi‐professional (General practitioner, clinical pharmacist and care homes staff) medication reviews during the 12‐month trial period. Target recruitment was 900 residents with 10% assumed loss to follow‐up. Co‐primary outcome measures were number of falls and potentially inappropriate prescribing assessed by the Screening Tool of Older Persons Prescriptions. Key findings: A total of 826 care home residents were recruited with 324 lost to follow‐up for at least one primary outcome measure. The mean number of falls per resident per annum was 3.3 for intervention and 3.0 for control ( P = 0.947). Each resident was found to be prescribed 0.69 (intervention) and 0.85 (control) potentially inappropriate medicines after 12 months ( P = 0.046). No significant difference identified in emergency hospital admissions or deaths. Estimated unadjusted incremental mean cost per resident was £374.26 higher in the intervention group. Conclusions: In line with other medication review based interventions in care homes, two MPMRs improved medication appropriateness but failed to demonstrate improvements in clinical outcomes. From a health system perspective costs where estimated to increase overall and therefore a different model of medicines management is required.